Landscapes (Dragway Productions, 2017)
If you think all transgender stories are the same - sex, transformation, mutilation, mental illness,... - you can't be more wrong ! Landscapes tells the story of four very different people, or better said, tells 4 different stories of a small group of friends living in rural areas, North East of Thailand (Isan). Their daily life is made of basic repetitive things: eating, sleeping, working, partying, dreaming. In a word, surviving, like we all do. But what we don't all do is having to cope with that peculiar feeling, that sensation that you will never be able to live your life fully, that you will never reach any level of happiness. A hard fate, for sure, but accepting that fate and agreeing to tell us what it means - even in a country, Thailand, where everybody says it's easier to be accepted when you are transgender (which is a false affirmation) - reveals extraordinary characters whose personal balance is always at risk. Sad but true, these stories are nevertheless also very positive as the message brought by these universal cameos is so powerful and sincere that you can only be touched. --